2021
DOI: 10.1371/journal.pone.0248075
|View full text |Cite
|
Sign up to set email alerts
|

The exposure risk to COVID-19 in most affected countries: A vulnerability assessment model

Abstract: The world is facing the coronavirus pandemic (COVID-19), which began in China. By August 18, 2020, the United States, Brazil, and India were the most affected countries. Health infrastructure and socioeconomic vulnerabilities may be affecting the response capacities of these countries. We compared official indicators to identify which vulnerabilities better determined the exposure risk to COVID-19 in both the most and least affected countries. To achieve this purpose, we collected indicators from the Infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
3
28
0
1
Order By: Relevance
“…Lastly, sociodemographic characteristics were the distal determinants, which may interfere in both the adoption of healthy behaviors and in emotional well-being [40]. In block 1, the following sociodemographic characteristics were considered: sex, age groups (12-15; 16-17 years old), skin color (white; non-white), mother's educational level (no college education, complete college education), family financial difficulties, and food insecurity ("Was there ever a concern that food would run out before your parents had money to buy more food?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, sociodemographic characteristics were the distal determinants, which may interfere in both the adoption of healthy behaviors and in emotional well-being [40]. In block 1, the following sociodemographic characteristics were considered: sex, age groups (12-15; 16-17 years old), skin color (white; non-white), mother's educational level (no college education, complete college education), family financial difficulties, and food insecurity ("Was there ever a concern that food would run out before your parents had money to buy more food?…”
Section: Discussionmentioning
confidence: 99%
“…During the period of social restraint measures, low-income families had more difficulties in facing the pandemic [40]. In Brazil, there was a greater reduction in family income among the poorest sections of the population, while informal workers were left without work, raising concerns about family maintenance and food insecurity [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many pandemic studies, including COVID-19 risk assessment studies, which suggested different prediction and mitigation models. [2][3][4][5] However, all these models are comparable to extinguishing a fire, which, of course, must be done immediately in order to survive. In this paper, we explore a Pandemic Risk Exposure Measurement (PREM) model 1 that identifies factors that influence a country's perceived vulnerability to pandemic risk exposure such as COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study predicted the infectious disease vulnerability index (IDVI) through an integrated modeling approach during the onset of coronavirus infection in Wuhan, China [ 77 , 78 , 79 ]. Multiple indicators such as travel information, country’s socio-economic condition, politics and health management facilities, and economic metrics are used to calculate IDVI scores [ 77 , 78 , 79 , 80 ]. IDVI scores range from 0 to 1, and a lower score signifies potential epidemic threats.…”
Section: Application Of Ai In Surveillance Of Covid-19mentioning
confidence: 99%